HTTP Adaptive Streaming – Where Is It Heading? - Timmerer, Christian; Hellwagner, Hermann (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
In this contribution, we present selected novel approaches and results of our research work in the ATHENA Christian Doppler Lab- oratory (Adaptive Streaming over HTTP and Emerging Networked Multimedia Services), a major research project at our department jointly funded by public sources and industry. By putting this work also into the context of related ongoing research activities, we aim at working out where HTTP Adaptive Streaming is currently heading.